Results in the Latin America and Caribbean Region 2021, Volume 17 - World Bank (World Bank, Washington, DC, 2022)
As a direct consequence of the COVID-19 pandemic, 2021was a year of enormous challenges in Latin America and the Caribbean (LAC). The region faced a daunting health emergency, for which it was ill prepared, and then endured the devastating social and economic costs of the crisis. LAC’s daunting challenge was to begin its social and economic recovery while still battling the pandemic. The World Bank supported these efforts and made a record contribution to the region’s countries, helping to mitigate the damage, protect the most vulnerable and support reconstruction efforts. The road to full recovery will still be long, and the region must continue to move toward more inclusive and resilient growth, deepening its capacity to absorb shocks and offering a greater well-being to its population. The briefs contained in this book showcase the many ways that both active and recently closed World Bank-financed projects are supporting the region’s efforts to overcome the current health crisis, and helping to lay foundations for long-term development, with inclusive growth, human capital creation and greater resilience. To promote inclusive growth, efforts were made to ensure that the benefits of investments in key sectors reach everyone. In the Brazilian state of Pernambuco, for example, a US$190 million loan helped finance investments in water supply and sanitation infrastructure, reducing water rationing for 900,000 people in Recife and connecting 70,000 people to the sewerage network. In northern Argentina, with a US358.8 million dollars loan from the Bank, investments were made along 418 kilometers of provincial roads, improving access and mobility for the area’s rural populations and indigenous communities. Human capital investments are fundamental for development. They help provide people with the tools they need to prosper and take advantage of available opportunities in a time of uncertainty and deep transformation in the world of work.